An Exploration of the Creative Process in Developing a Motion Graphics Biography of a Mathematics Pioneer - Rifani, Syifa Alifia; Maulana, Aris; Bilqisth, Lu’lu Qolbi; Safitri, Dewi (International Journal of Technology and Modeling, 2022)
This research explores the development of a motion graphics biography of a mathematics pioneer, using a collaborative approach between mathematicians and graphic designers. The research results highlight the successful integration of mathematical accuracy and creative visual elements, demonstrating interdisciplinary synergy. The development of a motion graphics prototype illustrates its potential to effectively convey complex mathematical concepts through dynamic visual narratives. Positive user experience feedback confirms the project's ability to maintain learner interest and engagement. Analysis of creative and technical challenges reveals the project's resilience in overcoming obstacles and adapting to complex technical constraints. Educational evaluations show a positive impact on students' mathematical understanding and interest. This research contributes not only to mathematical representation, but also to creative and educational approaches to mathematics. Recognition is given to collaborators, participants, and supporters who played a critical role in achieving these valuable results.